Evolução morfotectônica da porção centro-sul da Bacia Paraíba - Lima, Jean Carlos Ferreira de (2016)
Recent endogenous processes provide dynamic movements in the lithosphere and generate the varied forms of relief, even in areas of passive continental margins, such as the research area of this work located in northeastern Brazil. The reactivation of Precambrian basement structures, after the breakup between South America and Africa in the Cretaceous played an important role in the evolution of basins, which provided generated forms of relief. These morphodynamic characteristics can be easily observed in marginal basins that exhibit strong evidence fault reactivations. The purpose of this study is to investigate the influence of morphotectonic processes in the landscape structuring of Paraíba Basin. Therefore, we used aeromagnetic, high–resolution images of the Shuttle Radar Topographic Mission–SRTM, structural geological data, deep well data and geological field data. Based on the results of the data was observed that some preexisting structures in the crystalline basement coincide with magnetic and topographic lineaments interpreted as fault reactivation of the Post–Miocene units in the Paraíba Basin. Faults that offset lithostratigraphic units provided evidence that tectonic activity associated with the deposition and erosion in the Paraíba Basin occurred from Cretaceous to the Quaternary. The neotectonic activity that occurred in Paraíba Basin was able to influence the deposition of sedimentary units and landforms. It indicates that the deposition of post–Cretaceous units was influenced by reactivation of Precambrian basement structures in this part of the Brazilian continental margin.